ENHANCING WELL-BEING IN RETIREMENT: A SWOT ANALYSIS OF B40 PUBLIC RETIREES IN SABAH, MALAYSIA - Dzurizah Ibrahim; Jalihah Md Shah (Journal of Islamic, Social, Economics and Development, 2024)
The life transition of retirement is universal, yet the unique challenges and opportunities faced by B40 public retirees in Sabah, Malaysia, remain insufficiently understood. This knowledge gap hinders the development of targeted support systems crucial for enhancing the well-being of B40 retirees during their post-employment phase. It is the aim of the study to comprehensively explore the post-retirement experiences of B40 public retirees in Sabah, Malaysia. The research seeks to identify and analyze the strengths, weaknesses, opportunities, and threats (SWOT) that significantly influence the well-being of retirees in this demographic. A qualitative approach is employed, utilizing in-depth interviews as the primary method of data collection. The study focuses on 62 B40 retirees in the state of Sabah, Malaysia, using SWOT techniques to analyze the gathered qualitative data. The research reveals key strengths, including freedom from stress and emotional fulfillment, and identifies weaknesses, such as financial instability and challenges in adapting to a new lifestyle. Opportunities for retirees, such as post-retirement jobs and knowledge transfer, are uncovered, along with threats like financial hardships and depression. The implications of these findings extend to policymakers, financial planners, and individuals, emphasizing the necessity for a holistic and individualized approach to retirement planning. This research contributes valuable insights to the fields of industrial relations, gerontology, social work, and public policy, providing a foundation for developing targeted interventions that enhance the overall well-being of B40 retirees during their post-employment phase.